Die Bestudering van die Vakgeskiedenis – ’n Christelike Perspektief - de Klerk, J. H. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2003)
It has previously been argued that although one cannot speak of “Christian Mathematics” as such, it is definitely possible to have a Christian perspective on the mathematical sciences. Moreover, it is also possible to teach these subjects in a Christian way. As has been illustrated, one methodology of doing this is by using as framework the so-called viewpoint of science in context. However, some questions might be raised concerning this methodology; especially whether one has in fact succeeded in bringing a Christian perspective on the subject or whether one has only succeeded in giving a perspective next to the subject. The possibility of introducing the history of the subject – specifically Classical Mechanics in the present case – into the subject in order to give a sharper Christian perspective is discussed in this paper. The thesis is that introducing the history of the subject into the subject will help attaining a better perspective on the subject.